Evaluation of Strategies in the Management of Infective Aortic Valve Endocarditis at German Cardiac Surgical Departments - Akhyari, Payam; Aubin, Hug; Lühr, Maximilian; Rastan, Ardawan Julian; Beckmann, Andreas; Misfeld, Martin; on behalf of the Working Group Aortic Valve Surgery and the Board of Directors of the German Society for Thoracic Cardiovascular Surgery (The Thoracic and Cardiovascular Surgeon, 2019)
Background Surgical treatment of infective aortic valve endocarditis (AVE) remains a therapeutic challenge, necessitating interdisciplinary approach to limit morbidity and mortality in this high-risk cohort. With a considerable spectrum of available laboratory testings, imaging techniques, as well as operative strategies developed in recent years, there is a lack of standardization across cardiac surgical departments in Germany. Thus, the optimal treatment strategy of AVE has yet to be defined.Methods A nationwide survey on infective AVE was conducted, including 64 cardiac surgical departments responding to a 41-item questionnaire. The evaluation included common surgical practice, routine diagnostic steps, surgical techniques, perioperative medical treatment, as well as postoperative management.Results Remarkable differences were observed among the participating institutions, including the following components of the treatment: (1) standardization and extent of the use of imaging techniques and (2) success rate in identification AVE-causing germs, (3) timing of operation in case of cerebral embolization, and (4) choice of valve prosthesis for aortic valve replacement for infective AVE.Conclusion The findings of this survey underline the need for a nationwide registry to further elucidate the nature and course of AVE in Germany, as well as to serve as a solid basis for prospective trials, addressing the most important clinical purposes in the diagnosis and treatment of AVE.
Keywords: questionnaire; infective endocarditis; aortic valve; common practice; quality management